2014
DOI: 10.1088/0004-637x/783/1/8
|View full text |Cite
|
Sign up to set email alerts
|

ABUNDANCE PATTERNS IN THE INTERSTELLAR MEDIUM OF EARLY-TYPE GALAXIES OBSERVED WITHSUZAKU

Abstract: We have analyzed 17 early-type galaxies, 13 ellipticals and 4 S0's, observed with Suzaku, and investigated metal abundances (O, Mg, Si, and Fe) and abundance ratios (O/Fe, Mg/Fe, and Si/Fe) in the interstellar medium (ISM). The emission from each on-source region, which is 4 times effective radius, r e , is reproduced with one-or two-temperature thermal plasma models as well as a multi-temperature model, using APEC plasma code v2.0.1. The multi-temperature model gave almost the same abundances and abundance ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 82 publications
1
22
1
Order By: Relevance
“…These new results contradict previous papers (e.g. Rasmussen & Ponman 2009;Bregman et al 2010;Sun 2012;Yates et al 2017), which reported systematically lower Fe abundances in groups and/or ellipticals with respect to the hotter clusters of galaxies (although Konami et al (2014) reported similar average Fe abundances as reported here, albeit for ellipticals only). Rather than spex, most of those previous studies used many (very different) versions of apec to fit their data, making a direct comparison with this work difficult.…”
Section: Implications For the Iron Content In Ellipticals Groups Andcontrasting
confidence: 74%
“…These new results contradict previous papers (e.g. Rasmussen & Ponman 2009;Bregman et al 2010;Sun 2012;Yates et al 2017), which reported systematically lower Fe abundances in groups and/or ellipticals with respect to the hotter clusters of galaxies (although Konami et al (2014) reported similar average Fe abundances as reported here, albeit for ellipticals only). Rather than spex, most of those previous studies used many (very different) versions of apec to fit their data, making a direct comparison with this work difficult.…”
Section: Implications For the Iron Content In Ellipticals Groups Andcontrasting
confidence: 74%
“…The next generation of X-ray observatories, including Chandra, XMM-Newton and Suzaku, considerably increased the accuracy of these measurements (see e.g. Böhringer et al 2001;Molendi and Gastaldello 2001;Finoguenov et al 2002;Buote et al 2003;Sanders and Fabian 2006a;Werner et al 2006b;de Plaa et al 2006;de Plaa et al 2007;Rasmussen and Ponman 2007;Simionescu et al 2009;De Grandi and Molendi 2009;Bulbul et al 2012;Sasaki et al 2014;Konami et al 2014;Mernier et al , 2016aThölken et al 2016). The Reflection Grating Spectrometer (RGS) instrument onboard XMM-Newton allowed to formally identify C (Werner et al 2006a), N, and Ne (Xu et al 2002) emission lines in the ICM.…”
Section: Metals In the Icm: A Brief Historymentioning
confidence: 99%
“…From the density distribution, the temperature profile follows with the assumptions that the gas is in hydrostatic equilibrium and distributed isotropically (see Moster et al 2011). Every gas particle is also given initial metal abundances, such that the radial metallicity profile follows that of the stars, but with a slightly lower metallicity peak of 93% solar at the centre (following Konami et al 2014). The hot gas halo has the same spin parameter as the dark matter halo (λgas = 0.033).…”
Section: Initial Conditionsmentioning
confidence: 99%